Geochronology and Zr-in-rutile thermometry of high-pressure/low temperature metamorphic rocks from the Bantimala complex, SW Sulawesi, Indonesia - Boehnke, Mischa; Broecker, Michael; Maulana, Adi; Klemd, Reiner; Berndt, Jasper; Baier, Heidi (Lithos, 2019)
The timeframe of eclogite- and blueschist-facies metamophism in the central Indonesian region is poorly defined. Relative to its geographic extent, the regional coverage of isotopic age data is insufficient for an unambiguous interpretation of the geologic evolution of the Central Indonesian Accretionary Collision Complex. This study reports new geochronological constraints for high-pressure/low-temperature (HP/LT) rocks from the Bantimala Complex, SW Sulawesi, which further substantiate the importance of Cretaceous HP/LT metamorphism for the larger region. Multipoint Rb–Sr mineral isochrons of eclogites and glaucophane-rich rocks display a narrow range of white mica ages (130–120 Ma), interpreted to postdate peak-HP conditions, which is considerably smaller and more precise than the previously published K–Ar age spectrum (137–113 Ma). The close similarity with K–Ar ages suggests that these analyses were only slightly contaminated, if at all, with an extraneous Ar component, which did not significantly compromise the geological relevance of the existing dataset. An important result of this study is the emerging evidence for regional age differences between HP/LT rocks from SW Sulawesi (130–120 Ma) and Java (ca. 118 Ma). The existence of different subduction zones cannot be excluded but P–T and age differences between these occurrences can be reconciled with a model suggesting formation in the same subduction complex. Zircon is very rare in the studied HP/LT rock suite, but two glaucophane-rich rocks were suitable for U–Pb zircon dating and indicate Late Triassic–Early Jurassic protolith ages (ca. 205–185 Ma). The zircon population of a retrogressed eclogite records a more complex history including evidence for igneous crystallization, metamorphic recrystallization or growth, inheritance and variable degrees of Pb-loss. Metamorphic zircon rims mostly yielded U–Pb ages in the 135–110 Ma range that broadly confirm metamorphic ages determined by K–Ar and Rb–Sr white mica geochronology. Zircons that are significantly older (2.55–1.4 Ga and 400–260 Ma) than the protolith age are interpreted to represent detrital grains from subducted sediments that had been incorporated in mafic melts directly derived from a contaminated mantle source. The presence of continentally-derived detrital zircons that have presumably been included during melt formation in the mantle have not yet been described for any eclogite- and/or blueschist-facies rock of basaltic or gabbroic parentage.<br
CRIS-Team WoS Importer:2019-02-21
Keywords: Bantimala complex; Indonesia; Eclogite; Blueschist; Geochronology